Characterizing High-Growth Firms in New Zealand. (February 2013) - Hinton, Mark; Hamilton, R.T.
This study characterizes high-growth New Zealand-owned firms operating in business-to-business relationships. Within a case study design featuring six such firms, four dimensions emerged that captured their key features: founders' characteristics; opportunity orientation; opportunity exploitation; and the management of growth. All the firms had joint founders who brought complementary skills and maintained external advice networks. The growth opportunities leveraged innovations of other firms. Exploitation was in niche areas in which there were both few competitors and small numbers of larger customers, facilitating intensive relationship marketing. The founders managed the businesses by developing a pro-growth culture among employees, but supported this through strong financial control systems and low debt preference. The lack of evidence on the characteristics of this important group of firms has contributed to poorly targeted policy. This paper begins to redress this situation.